Nizamul Mulk dan Madrasah Nizamiyah Relasi Lembaga Pendidikan dan Penguasa (Madrasah dan Otodoksi Pendidikan) - Kamsi, Nur Lila (Edification Journal : Pendidikan Agama Islam, 2022)
Islamic educational institutions are always developing in line with the needs and changes of society. The development of society is marked by the progress of science and the need to preach Islam. In the 5th century Hijriyah, at the time the madrasa was founded, the scientific development of the community, especially Muslims, could be said to have reached a perfect stage, because almost all knowledge, both al-ulum an-naqliyah and al-ulum al-aqliyah, had been compiled and systematized. Reviewing Nizhamiyah using library research through various reference sources, journals, relevant books. In this study, it is explained that nizamiyah is an educational institution in the form of a madrasa, this madrasa was founded in the city of Baghdad, founded by a prime minister who has great attention to science and education in addition to political and religious factors that use the modern system. By using a socio-political approach, this study seeks to trace the birth of the Nizhamiyah madrasa with a multi-motivation background. With its teacher council based on the Shafi'i madhhab, the Nizamiyya madrasa is seen as the embodiment of the triumph of the theological-dogmatic movement that works hand in hand with the Sunni school of thought to balance the dominance of the Mu'tazilah-Hambali ideology and the dominance of the Shi'ites. So that the subjects of study are Asy'ariyah and fiqh-oriented. The realm of "intellectualism" is lost in the educational process of this madrasa. However, Nizhamiyah is still understood as the most important Islamic educational institution and a model in the study of the social history of Islamic education.